Genet: Automatic Curriculum Generation for Learning Adaptation in Networking - Xia*, Zhengxu; Zhou*, Yajie; Yan, Francis Y.; contribution), Junchen Jiang (*equal (ACM Special Interest Group on Data Communication Conference (SIGCOMM ’22), 2022)
As deep reinforcement learning (RL) showcases its strengths in networking, its pitfalls are also coming to the public's attention. Training on a wide range of network environments leads to suboptimal performance, whereas training on a narrow distribution of environments results in poor generalization. This work presents Genet, a new training framework for learning better RL-based network adaptation algorithms. Genet is built on curriculum learning, which has proved effective against similar issues in other RL applications. At a high level, curriculum learning gradually feeds more "difficult" environments to the training rather than choosing them uniformly at random. However, applying curriculum learning in networking is nontrivial since the "difficulty" of a network environment is unknown. Our insight is to leverage traditional rule-based (non-RL) baselines: If the current RL model performs significantly worse in a network environment than the rule-based baselines, then further training it in this environment tends to bring substantial improvement. Genet automatically searches for such environments and iteratively promotes them to training. Three case studies—adaptive video streaming, congestion control, and load balancing—demonstrate that Genet produces RL policies that outperform both regularly trained RL policies and traditional baselines.